Scientific generalizing of modern approaches to routine immunization over the world - А. А. Kotvitska; O. V. Kononenko; I. V. Kubareva (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. The experience of the routine population vaccination in 53 countries of Europe, including Ukraine has been generalized in the article.